Multiorgan resection for mucinous cystic neoplasms of the pancreas: Case report [Pankreasin müsi̇nöz ki̇sti̇k neoplazi̇si̇nde multi̇organ rezeksi̇yonu: Olgu sunumu] - (:unkn) unknown (My University, 2008)
Mucinous cystic neoplasms of the pancreas account about 9.7 % of all pancreatic cysts. Treatment of the disease, which affects women 10 times more often than men, is complete surgical resection. In this case, besides pancreas, spleen, transverse colon, small intestine and left adrenal gland were also resected and a literature search was undertaken.
Keywords: Mucinous cystic neoplasm; Multiorgan resection; Pancreas